POLA PERESEPAN TERAPI ANTIDIABETES ORAL DI PUSKESMAS IMOGIRI BATUL - Amalina, Adila Nur; Risa, Mexsi Mutia (Talenta Publisher, 2025)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. The prevalence of diabetes mellitus in Indonesia continues to increase and is included in the top 10 diseases at the health center in Bantul Regency. In addition, diabetes mellitus is also included in the top 5 diseases at the Imogiri I Health Center. The purpose of this study was to find out the description of type II diabetes mellitus drug prescription at the Imogiri I Health Center for the period August - December 2022. This study used a non-experimental descriptive method by collecting retrospective medical records of patients with diabetes mellitus type II. The data obtained were then analyzed in a quantitative descriptive manner presented with percentages in the form of diagrams. The results showed that most patients with type II diabetes mellitus were female (31%) with the most age range being 46-65 years (57%). The description of drug prescribing for type II diabetes mellitus patients at the Imogiri I Health Center consists of the use of diabetes mellitus drugs alone, namely the biguanid group (Metformin) as much as 95% and the sulfonylurea group (Glimepirid) as much as 5%. It can be concluded that the drug most often prescribed to patients with diabetes mellitus type II at the Imogiri I Public Health Center with a single treatment is metformin as much as 95% which belongs to the biguanide group.